The Feasibility of Comic Media on Narrative Texts Based on Local Wisdom in VII Grade Student of Junior High School (SMPN) 3 Kotapinang - Asri Yulianda; Biner Ambarita; Khairil Ansari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aims of this study is to find out the feasibility of comic media on narrative texts based on local wisdom. The research was conducted in the second semester 2018/2019. The subjects in this study were students of VII grade  of Junior High School (SMPN) 1 Kotapinang. The results of the material expert validation on the feasibility of material aspects gained an average of 89.37% with the category "Very Good", the aspect of language feasibility obtained an average of 83.33% with the category "Very Good", the feasibility of presentation aspects obtained an average of 89, 58% with the category "Very Good. The results of the validation from the illustrated expert obtained an average of 100% with the category "Very Good", while the results of the validation of the design of the learning media from the visual appearance aspect obtained an average of 80.28% with the category "Good", while from the aspect of design learning obtained on average 75% with the category "Good". Therefore, comic media in narrative texts based on local wisdom are developed for VII Grade Students of Junior High School (SMPN) 3 Kotapinang that are suitable for use in the learning process.